Theorizing a Hybrid Feminism: Motherhood in Margarita Nelken's En torno a nosotras (1927). Issue 2 (February 2016) - Bender, Rebecca M.
Abstract : This essay explores the complex feminist philosophy that comes to the fore in En torno a nosotras, an overlooked novel written by Margarita Nelken, one of early twentieth-century Spain's most vocal and polemic feminists. The analysis juxtaposes the novel with Nelken's essays, La condición social de la mujer en España and La mujer ante las cortes constituyentes, in order to encourage a hybrid interpretation of first-wave feminist thought in Spain. Specifically, this essay concentrates on the incorporation of maternity and motherhood into modern female identities. It provides a thorough examination of the debate, defence and theorization of this traditional female role within a fictional novel by considering the implications of Platonic and Socratic dialogues. The resulting analysis argues for a re-evaluation of first-wave Spanish feminism that takes into account both liberal and conservative tendencies.